Governing heatwaves in Europe: comparing health policy and practices to better understand roles, responsibilities and collaboration - Vanderplanken, Kirsten; van den Hazel, Peter; Marx, Michael; Shams, Ahmad Zia; Guha-Sapir, Debarati; van Loenhout, Joris Adriaan Frank (Health research policy and systems, 2021)
The expectation that climate change will further exacerbate extreme weather events such as heatwaves is of primary concern to policymakers and scientists. Effective governance is fundamental to preparedness for and response to such threats. This paper explores the governance structures of European heat health action plans and provides insights into key stakeholders, roles, responsibilities and collaboration.
Gesehen am 30.03.2021